Español (XXI Century. Spanish Literature and Culture, 2018)
The short stories included in Hijos sin hijos (1993), by Enrique Vila-Matas, are unique in the Contemporary Spanish Narrative. The two references implied in the text are contemporary history and the life and works of Franz Kafka. The first is cambiguous or of little importance; and the second appears tranferred to the fictitious characters. The unique, the rare and the extravagant are prominent in these narrations that, at the end, are far away from realism.
Keywords: Contemporary Spanish Short Story; Kafka Recepction; History and Fiction.